Lost Hope in Hemingway`s A Farewell to Arms: Existentialism Study - Mahnaz Soqandi; Shiva Zaheri Birgani (Britain International for Academic Research (BIAR) Publisher, 2020)
This research paper attempts to explore the novel, A Farewell to Arms through the lens of Existential approach and it explores the role played by Existentialism in the novel. Hemingway is one of the greatest American writers in the twentieth century. A Farewell to Arms, his most famous anti-war novel. An American volunteer joining Italian army falls in love with a British nurse but their love is destroyed mercilessly by the war. Hemingway expresses his outlooks on the world, on life and on individual in this novel. The world under Hemingway’s pen is a chaotic and irrational world. People living in this world discard traditional values and faith, living a nihilistic and miserable life. Although the world is absurd and life is nihilistic, the protagonist has fighting spirit. He actively participates in life and pursues the meaning of life. He fights courageously against the danger and death in adversity to realize his existential values. These views are in accordance with existentialist philosophy rising in the twentieth century. Existentialism mainly explores human existence, the absurdity of the world and the meaninglessness and purposelessness of life. Meanwhile it greatly emphasizes man’s freedom of choice and action. Living in a chaotic and absurd world, man can never get rid of the sense of nihility. Man has to face it bravely. There is existentialist tendency in A Farewell to Arms, and Hemingway is indeed a writer with existentialist thought.